Does Hospital Disaster Preparedness Predict Response Performance During a Full-scale Exercise? A Pilot Study. Issue 5 (5th August 2014) - Djalali, Ahmadreza; Carenzo, Luca; Ragazzoni, Luca; Azzaretto, Massimo; Petrino, Roberta; Della Corte, Francesco; Ingrassia, Pier Luigi
Abstract: Introduction: The assessment of hospital disaster preparedness and response performance is a way to find and remove possible gaps and weaknesses in hospital disaster management effectiveness. The aim of this pilot study was to test the association between the level of preparedness and the level of response performance during a full-scale hospital exercise. Method: This pilot study was conducted in a hospital during a full-scale exercise in the Piedmont region of Italy. The preparedness evaluation was conducted by a group of three experts, three days before the exercise, and the response evaluation was conducted during the exercise. The functional capacity module was used for preparedness evaluation, and the response performance of the "command and control" function of the hospital was evaluated by nine semiquantitative performance indicators. Results: The preparedness of the chosen hospital was 59%, while the response performance was evaluated as 70%. The hospital staff conducted Simple Triage and Rapid Transport (START) triage while they received 61 casualties, which was 90% correct for the yellow group and 100% correct for the green group. Conclusion: This pilot study showed that it is possible to use standardized evaluations tools, to simultaneously assess the relationship between preparedness elements and response performance measures. An experimental study including a group of hospitals, also using more comprehensive evaluation tools, should be done to evaluate the correlation between the level of preparedness and the response performance of a hospital, and the impact of hospital disaster planning, on the outcome of disasters victims. A Djalali, L Carenzo, L Ragazzoni, M Azzaretto, R Petrino, F Della Corte, PL Ingrassia .Does hospital disaster preparedness predict response performance during a full-scale exercise? A pilot study .Prehosp Disaster Med .2014 ;29 (4 ):1 -7 .